EXPERIENCE OF REVISION HIP ARTHROPLASTY AT THE PROLAPSE OF THE ACETABULAR COMPONENT INTO THE SMALL PELVIC CAVITY - V. M. Mashkov; V. V. Dolgopolov (Travmatologiâ i Ortopediâ Rossii, 2011)
The successful experience of revision arthroplasty at acetabular component instability complicated by its prolapse into the small pelvic cavity. The authors underline the need for a comprehensive preoperative examination of patients in preparation for revision surgery, careful planning of the operation and dynamic observation of patients in the postoperative period.